2010
DOI: 10.1111/j.1365-2133.2010.10087.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in allergen content over time of acrylates/methacrylates in patch test preparations

Abstract: SummaryBackground Acrylates ⁄methacrylates are volatile substances. There might be a gradual decrease in acrylate ⁄methacrylate allergen content over time in patch test preparations but this has not yet been documented. Objectives To determine the allergen content of acrylates ⁄methacrylates in patch test preparations over time under different storage conditions. Methods Five acrylate ⁄methacrylate allergens [2-hydroxyethyl methacrylate (2-HEMA), methyl methacrylate (MMA), ethylene glycol dimethacrylate (EGDMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 13 publications
(28 reference statements)
3
53
0
1
Order By: Relevance
“…9 This same study showed that, when stored in IQ chambers, the concentration dropped to less than 80% of initial concentration by 1 day if stored at room temperature and by 2 days if refrigerated. One study showed that the compound is stable for up to 256 days when stored in polypropylene syringes in either a refrigerator or a freezer but not if stored at room temperature.…”
Section: Acrylatesmentioning
confidence: 88%
See 4 more Smart Citations
“…9 This same study showed that, when stored in IQ chambers, the concentration dropped to less than 80% of initial concentration by 1 day if stored at room temperature and by 2 days if refrigerated. One study showed that the compound is stable for up to 256 days when stored in polypropylene syringes in either a refrigerator or a freezer but not if stored at room temperature.…”
Section: Acrylatesmentioning
confidence: 88%
“…It was shown to be stable for up to 325 days when stored in polypropylene syringes in a refrigerator or a freezer. 9 When stored in IQ or IQ Ultimate chambers, the concentration of 2-HPA decreased to less than 80% of initial concentration by 72 hours if refrigerated and by 8 hours when kept at room temperature. When the syringes were stored in room temperature, the concentration decreased to less than 80% initial concentration by 21 days.…”
Section: Acrylatesmentioning
confidence: 98%
See 3 more Smart Citations